2009
DOI: 10.1111/j.1365-2702.2009.02853.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic relationships in day surgery: a grounded theory study

Abstract: Title: Therapeutic Relationships in Day Surgery: A Grounded Theory study. Aim: The aim of the study was to explore patients' experiences of day surgery.Background: Therapeutic relationships are considered to be a core dimension of nursing care. However in modern healthcare with short hospital stays the formation of these relationships may be impeded. A major theme to emerge from this study was the development of therapeutic relationships in the day surgery setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…Mottram expressed that some nurses’ behaviors such as adequate explanation, timely satisfaction of patient’s requests, intimacy and a friendly interaction with the patient are characteristics of therapeutic communication in nursing care. 27 In Finch’s study, patients expected a professional, respectful, intimate, and professional behavior from nurses. 28 Nestel and Kidd believed that listening actively, speaking clearly and behaving respectfully were verbal and nonverbal skills crucial to effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…Mottram expressed that some nurses’ behaviors such as adequate explanation, timely satisfaction of patient’s requests, intimacy and a friendly interaction with the patient are characteristics of therapeutic communication in nursing care. 27 In Finch’s study, patients expected a professional, respectful, intimate, and professional behavior from nurses. 28 Nestel and Kidd believed that listening actively, speaking clearly and behaving respectfully were verbal and nonverbal skills crucial to effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…In the day case surgery setting, spiritual expressions may be connected with existential aspects or with fear and patients may wish to connect with the surgical staff. Staff should be aware of this, since at present, the results of this research indicate that staff are not always aware of their therapeutic potential, a finding that has been identified previously by Mottram [18].…”
Section: Recommendationsmentioning
confidence: 61%
“…Data from this same study demonstrated that the nurses had managed, on the whole, to humanise the day surgery process against all the odds (Mottram, 2009 With many press reports of hospital acquired infection it is little wonder that cleanliness was very important to patients and was often a major reason for patients' preference for day surgery: the shorter time you are in the less time you have to acquire an infection.…”
Section: Time As a Conveyor Beltmentioning
confidence: 89%